Cybersecurity Vulnerabilities in Healthcare: A Threat to Patient Security - Triplett, William J. (Cybersecurity and Innovative Technology Journal, 2024)
Healthcare information systems hold significant importance; hence, their cybersecurity is crucial. Exposed networks make it easy for cybercriminals to launch cyberattacks and access healthcare data. Thus, concerns regarding cybersecurity and its link to healthcare privacy, confidential data, and medical devices are growing. Therefore, cybersecurity vulnerabilities in healthcare and patient security are significant issues. Healthcare information systems comprise correlated networks and play a vital role in treating and saving patients. However, advanced circulated ransomware attacks on hospitals prevent access to electronic health records for providing appropriate patient care, thus forcing doctors to turn to other facilities. These cyberattacks can leak patient data, and regaining control of information systems and patient data is highly expensive, thus resulting in extensive monetary losses. Cyberattacks aimed toward electronic medical records, information technology systems, and medical devices have corrupted the best systems across clinics and small offices with physicians, as well as merged health systems. There is an urgency to address cybersecurity vulnerabilities in healthcare; however, opinions differ regarding suitable measures for safeguarding patient data and ensuring infrastructural security. We aimed to reconcile these diverging hypotheses and provide an understanding of the current landscape and directions for further improvements by reviewing several studies on healthcare cybersecurity. We also interviewed healthcare professionals, cybersecurity experts, and administrators and distributed a survey questionnaire to healthcare organizations to gather quantitative data on existing cybersecurity measures and vulnerabilities. Our analyses show that healthcare organizations are vulnerable to a variety of threats, cyberattacks disrupt the health sector, cybersecurity vulnerabilities impact patient security, and implementations of cybersecurity measures are inconsistent across organizations. Owing to the sophisticated nature of cyberattacks, the healthcare industry must prioritize cybersecurity and provide the funding required to develop critical systems for safeguarding patients and their data. The study's findings underscore the need for standardized cybersecurity practices in healthcare to address inconsistencies in measures across organizations. Adequate and ongoing investment in cybersecurity infrastructure is imperative to counter increasingly sophisticated cyberattacks. Additionally, protecting patient data and maintaining trust within the healthcare sector are ethical imperatives that should guide industry actions. By embracing these implications, the healthcare industry can enhance patient security, financial stability, and ethical integrity.